In situ Raman and UV-Vis spectroscopic analysis of lithium-ion batteries. Issue 1773 (2015) - Heber, Marcel; Schilling, Christian; Gross, Toni; Hess, Christian
ABSTRACT: The potential of Raman and UV-Vis diagnostics for spatially-resolved and in situ diagnostics of lithium-ion batteries is demonstrated. Regarding the use of in situ Raman diagnostics focus is put on LiCoO2 electrode materials, which were investigated in detail as composites of LiCoO2 with binder and conductive additives. The potential of in situ UV-Vis analysis is illustrated for carbon-based materials showing significant absorption changes during electrochemical cycling due to lithium de-/intercalation.